Selectivity of the binary stationary phase of cucurbit[7]uril with ionic liquid in gas chromatography. Issue 93 (11th October 2015) - Wang, Yingzhen; Qi, Meiling; Fu, Ruonong
<x xml:space="preserve">Abstract</x> The binary stationary phase of CB7 in an ionic liquid shows high selectivity and resolving ability for diverse analytes via multiple molecular interactions and unique retention mechanism.